CONTROLLED-RELEASED ORAL MELATONIN SUPPLEMENTATION FOR HYPERTENSION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (June 2022) - Kam, Eric; Lee, Pui; Poon, Paul; Yu, Chun-Pong; Lee, Vivian; Chung, Vincent Ch; Wong, Samuel Ys
Abstract : Objective: Oral melatonin is a potential alternative treatment for hypertension, but high-quality and relevant meta-analyses have not yet been conducted. This meta-analysis aimed to investigate whether oral melatonin supplementation could reduce daytime/asleep blood pressure, reduce cardiovascular risks, improve sleep quality, and if it is well-tolerated compared with placebo. Design and method: Relevant articles were searched in multiple databases, including MEDLINE, EMBASE, CINAHL Complete, and Cochrane Library, from their inception to June 2021. The included studies were randomized controlled trials that recruited patients with hypertension, using oral melatonin as the sole intervention, and investigated its effect on blood pressure. The mean out-of-office (including 24-h, daytime, and asleep) systolic blood pressure and diastolic blood pressure, sleep quality, and side effects were compared between the melatonin and placebo arms using pairwise random-effect meta-analyses. The risk of bias assessment was conducted using the Cochrane risk-of-bias tool. Results: Four studies were included; only one study was considered to have a low risk of bias. No study reported cardiovascular risk or outcomes. Only controlled-release melatonin (but not immediate-release preparation) reduced asleep systolic blood pressure by 3.57 mm Hg (95% confidence interval: -7.88–0.73; I2 = 0%). It might also reduce asleep diastolic blood pressure and awake diastolic blood pressure, but these differences did not reach statistical significance. Melatonin may improve sleep efficacy and total sleep time and is safe and well-tolerated. Conclusions: Due to the limited number of high-quality trials, the quality of evidence was low to very low high-quality and adequately powered randomized controlled trials on melatonin are urgently needed.